Effectiveness of Lifelong ART (Option B+) in the Prevention of Mother-to-Child Transmission of HIV Programme in Zambia: Observations Based on Routinely Collected Health Data - Brian Muyunda; Brian Muyunda; Patrick Musonda; Paul Mee; Jim Todd; Charles Michelo (Frontiers Media S.A., 2020)
Background: Mother to child transmission of HIV (MTCT) is a global challenge affecting many countries especially in sub-Saharan Africa. In 2009 about 370,000 infants were infected with HIV mainly through MTCT and most of them in sub-Saharan Africa. We aimed to determine the effectiveness of Option B+ compared to other options in reducing rates of early MTCT of HIV infections in Zambia.Methods: This was a retrospective cohort study based on routinely collected data using SmartCare in Zambia. Survival analysis with Cox Proportional Hazard regression was used to determine association between MTCT and regimen type of mothers. Kaplan-Meier (K-M) curves were used to compare MTCT for infants born to mothers option B+ to those on other options, and Wilcoxon (Breslow) test was used to establish statistical significance.Results: Overall (n = 1,444), mother-baby pairs with complete data were included in the analysis, with the median age of mothers being 33 (28-38) years; and 57% of these women were on Option B+. MTCT rate was estimated at 5% (73/1,444) [P = 0.025]. A Kaplan-Meier estimate showed that HIV Exposed Infants (HEI) of mothers on Option B+ had lower MTCT rate than those who were on other MTCT prevention interventions [Wilcoxon test; chi2 = 4.97; P = 0.025]. Furthermore, The Nelson Aalen cumulative hazard estimates indicated similar evidence of option B+ being more effective than other options with some statistical significance [HR = 0.63, P = 0.068]. HEI of option B+ mothers had 50% reduced risk of having HIV infection compared to option A/B [adjusted HR = 0.4; 95% CI = 0.28-0.84; P = 0.010]. HEI to women who were married had an increased risk 50% of getting infected compared to those not married [adjusted HR = 1.5; 95% CI = 3.43-6.30; P < 0.001]. Exposed infants whose mothers had assisted delivery had 3 times increased risk of getting infected compared to those born through normal vaginal delivery [Adjusted HR = 3.2; 95% CI = 0.98-10.21; P = 0.050].Conclusions: The use of Option B+ as PMTCT intervention was found to be more effective in reducing MTCT of HIV compared to other options. Scaling up access to life-long ART and improving retention for women on treatment can potentially reduce further vertical transmission.